Biobehavioral Insights into Adaptive Behavior in Complex and Dynamic Operational Settings: Lessons learned from the Soldier Performance and Effective, Adaptable Response Task - Haufler, Amy J.; Lewis, Gregory F.; Davila, Maria I.; Westhelle, Felipe; Gavrilis, James; Bryce, Crystal I.; Kolacz, Jacek; Granger, Douglas A.; McDaniel, William (Frontiers in Medicine, 2018)
The purpose of this study was to explore the biobehavioral correlates of adaptive behavior in the context of a standardized laboratory-based mission-relevant challenge (the Soldier Performance and Effective, Adaptable Response Task, SPEAR). Participants were 26 healthy male volunteers (M=34.85 yrs, SD=4.12) with active military duty and leadership experience within the last 5 years (i.e., multiple leadership positions, operational deployments in combat, interactions with civilians and partner nation forces on the battlefield, experience making decisions under fire). The SPEAR task simultaneously engages perception, cognition, and action aspects of human performance demands similar to those encountered in the operational setting. Participants must engage with military-relevant text, visual, and auditory stimuli, interpret new information, and retain the commander’s intent in working memory to create a new plan of action for mission success. Time-domain measures of heart period (HP) and respiratory sinus arrhythmia (RSA) were quantified, and saliva was sampled (later assayed for cortisol and alpha-amylase, sAA) before- during- and post-SPEAR.  Results revealed a predictable pattern of withdraw and recovery of the cardiac vagal tone during repeated presentation of battlefield challenges. Recovery of vagal inhibition following executive function challenge was strongly linked to better task-related performance. Rate of RSA recovery was also associated with better recall of the Commander’s intent. Decreasing skin conductance response magnitude prior to the task was positively associated with better overall task-related performance.  Lower levels of RSA were observed in participants who reported higher rates of combat deployments, and reduced RSA flexibility was associated with higher rates of casualty exposure. Greater RSA flexibility during SPEAR was associated with greater self-reported resilience. There was no consistent pattern of task-related change in cortisol or sAA. We conclude that individual differences in psychophysiological reactivity and regulation in response to an ecologically valid, military-relevant task are associated with performance-related adaptive behavior in this standardized operational setting. The implications for modern day warfare, where advancing our understanding of the nature of individual differences in adaptive problem solving is critical to mission success, fitness for duty, and other occupational health-related outcomes, are discussed.